Emerging common molecular pathways for primary dystonia. Issue 7 (25th July 2013) - LeDoux, Mark S.; Dauer, William T.; Warner, Thomas T.
ABSTRACT The dystonias are a group of hyperkinetic movement disorders whose principal cause is neuron dysfunction at 1 or more interconnected nodes of the motor system. The study of genes and proteins that cause familial dystonia provides critical information about the cellular pathways involved in this dysfunction, which disrupts the motor pathways at the systems level. In recent years study of the increasing number of DYT genes has implicated a number of cell functions that appear to be involved in the pathogenesis of dystonia. A review of the literature published in English‐language publications available on PubMed relating to the genetics and cellular pathology of dystonia was performed. Numerous potential pathogenetic mechanisms have been identified. We describe those that fall into 3 emerging thematic groups: cell‐cycle and transcriptional regulation in the nucleus, endoplasmic reticulum and nuclear envelope function, and control of synaptic function. © 2013 Movement Disorder Society